Factors Associated with the Incidence and Mortality of Coronavirus Disease 2019 (COVID-19) after 126-million Cases: A Meta-analysis - Jeerath Phannajit; Kullaya Takkavatakarn; Pisut Katavetin; Thanin Asawavichienjinda; Kriang Tungsanga; Kearkiat Praditpornsilpa; Somchai Eiam-Ong; Paweena Susantitaphong (Springer, 2021)
Objectives: This meta-analysis was conducted to investigate the current global incidence and mortality of COVID-19 and also explored the associated factors including geographic variations, transmission scenarios, country economic status, and healthcare performance. Methods: The search was conducted in online databases based on reports from national authorities by March 28, 2021. Random-effects model meta-analyses and meta-regression analyses were used to generate summary estimates and explored sources of heterogeneity. Results: The cumulative number of confirmed COVID-19 cases was 125,704,789 reported by 216 countries. The pooled Daily Cumulative Index (DCI) was 1423.87 cases/day which was highest in South America (2759.15 cases/day) followed by North America (2252.49 cases/day), Europe (1858.44 cases/day), Asia (1484.84 cases/day), Africa (193.09 cases/day), and Australia/Oceania (18.55 cases/day). The overall pooled mortality rate of COVID-19 was 1.53%. Higher income countries and countries with community transmission had higher DCI. By meta-regression, country total health expenditure per capita, percentage of universal health coverage, and total number of tests were associated with higher DCI. On the contrary, country Gross Domestic Product (GDP) per capita were negatively correlated with mortality rate. Conclusion: To date, 216 countries around the world are affected by COVID-19. Higher income, GDP, and countries' investments on heath are associated with higher DCI while higher GDP correlates with lower mortality. Community transmission route have more impact on the incidence and mortality of COVID-19.